Caffeine increases food intake while reducing anxiety-related behaviors. (1st June 2016) - Sweeney, Patrick; Levack, Russell; Watters, Jared; Xu, Zhenping; Yang, Yunlei
Abstract: The objective of this study was to determine the effects of different doses of caffeine on appetite and anxiety-related behavior. Additionally, we sought to determine if withdrawal from chronic caffeine administration promotes anxiety. In this study, we utilized rodent open field testing and feeding behavior assays to determine the effects of caffeine on feeding and anxiety-related behavior (n = 8 mice; 4–8 weeks old). We also measured 2 h and 24 h food intake and body-weight during daily administration of caffeine (n = 12 mice; 4–8 weeks old). To test for caffeine withdrawal induced anxiety, anxiety-related behavior in rodents was quantified following withdrawal from four consecutive days of caffeine administration (n = 12 mice; 4–8 weeks old). We find that acute caffeine administration increases food intake in a dose-dependent manner with lower doses of caffeine more significantly increasing food intake than higher doses. Acute caffeine administration also reduced anxiety-related behaviors in mice without significantly altering locomotor activity. However, we did not observe any differences in 24 h food intake or body weight following chronic caffeine administration and there were no observable differences in anxiety-related behaviors during caffeine withdrawal. In conclusion, we find that caffeine can both increase appetite and decrease anxiety-related behaviors in a dose dependent fashion. Given the complex relationship between appetite and anxiety, the present study provides additional insights into potential caffeine-based pharmacological mechanisms governing appetite and anxiety disorders, such as bulimia nervosa.